2018
DOI: 10.7441/joc.2018.03.10
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Perception of Private Label Products: An Empirical Research

Abstract: This article analyzes the attitudes of consumers towards the purchase of private label products, considering their needs and requirements, the type of purchased product, reasons for the purchase, as well as demographic characteristics of the respondents. The main aim of the research is to determine the factors and variables that significantly influence and shape the consumer's perception and attitude towards the purchase of private label products. The perception of private label products by Slovak consumers wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 15 publications
1
43
0
6
Order By: Relevance
“…The questionnaire research done by authors on ,,consumer perceptions of private label products showed the price as the most important factor in purchasing private label products. The researchers focused on the change in preferences of purchased products considering gender, age, education, income, and consumer status of respondents" [6]. One of the first papers which ,,investigate the link between corporate governance and gender equality in companies on the Bratislava Stock Exchange is named gender equality and corporate governance in Slovakia.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The questionnaire research done by authors on ,,consumer perceptions of private label products showed the price as the most important factor in purchasing private label products. The researchers focused on the change in preferences of purchased products considering gender, age, education, income, and consumer status of respondents" [6]. One of the first papers which ,,investigate the link between corporate governance and gender equality in companies on the Bratislava Stock Exchange is named gender equality and corporate governance in Slovakia.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Nearly 70% of seniors said they preferred quality over price. The importance of quality was confirmed by Valaskova, Kliestikova and Krizanova (2018), what may cause seniors to tend to be more loyal to selected products or brands. The survey confirmed that seniors are less emotionally stable, so the packaging of dairy products is essential in their decision making.…”
mentioning
confidence: 93%
“…Despite the fact that the number of socially responsible companies in Slovakia is relatively low, it has an increasing character. Companies are aware of their negative impact on the environment and seek to eliminate it through the principles of corporate social responsibility, thereby increasing their competitiveness, image and customer loyalty [6,7].…”
Section: Introductionmentioning
confidence: 99%